Harnessing multi-country cooperations, initiatives, facilities, and technologies for advancing livestock genetic improvement in Africa - Mapholi, N.O.; Banga, C.; Mrode, Raphael A.; Opoola, O.; Houaga, I.; Nesengani, L.T.; Ibeagha-Awemu, E.M. (Springer, 2025)
Multi-country initiatives have facilitated the development and adoption of technologies in developed nations, but such cooperations are less evident in Africa. National breed-specific genetic evaluations have been the most commonly practiced globally; however, there has been a growing interest and opportunities have arisen for across-country collaborations, or international consortiums combining data into large-scale multi-country genetic evaluations to achieve better genetic gains. Despite the need to establish multi-country genetic evaluation schemes for livestock production suitable for the African continent, few initiatives have been put in place to achieve this. This chapter draws attention to multi-country initiatives and benefits for performance recording as well as success stories in Africa (Sect. 29.2), the benefits of data sharing (Sect. 29.3), the role and importance of core facilities, especially those associated with the technologies of genomics, proteomics, metabolomics, metagenomics, and statistical/bioinformatics management of data (Sect. 29.4), germplasm centers for the storage of genetic materials or seed stock (Sect. 29.5), and the important place and prospect of multi-country genetic evaluations and practical application in Africa (Sects. 29.6 and 29.7). Such initiatives may provide an opportunity for genetic improvement of indigenous livestock populations and the possibility to open up new markets for African germplasm as well as inter-country germplasm trade within the continent. This would have a positive impact on the continent’s livestock economy.